2019
DOI: 10.4103/njs.njs_22_19
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width: A surrogate biomarker to predict tumor burden in carcinoma gallbladder

Abstract: Aim:To assess the role of red cell distribution width as a marker to predict tumor burden in gallbladder cancer (GBC).Methods:One hundred and twenty-eight patients with newly diagnosed GBC were included in the study. Peripheral blood samples were obtained, and red cell distribution width (RDW) was assessed. Tumor markers and other biochemical parameters were also recorded.Statistical Analysis:Quantitative variables were summarized using mean and standard deviation or median and interquartile range based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…RDW values of ≤ 12.9 were categorized as normal and values ≥ 13.0 were considered elevated. Stroke severity (NIHSS) was categorized as mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe , and mRS ≪ 2 (0,1, and 2) was defined as a fine outcome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RDW values of ≤ 12.9 were categorized as normal and values ≥ 13.0 were considered elevated. Stroke severity (NIHSS) was categorized as mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe , and mRS ≪ 2 (0,1, and 2) was defined as a fine outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Red cell distribution width (RDW) is a hematologic parameter that indicates the divergence of red blood cell volume. Increases in RDW have been found in different physiological and pathological conditions such as pregnancy, vitamin B12 and folate deficiency, malignancy, idiopathic pulmonary fibrosis and coronary artery disease [7][8][9][10][11][12]. Although RDW was created for the diagnosis of different types of anemia, recent research has revealed its predictive role in cerebrovascular diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…RDW values of ≤12.9 were categorized as normal and values ≥13.0 were considered elevated. Stroke severity (NIHSS) was categorized as mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe , and mRS <<2 (0,1, and 2) was de ned as a ne outcome.…”
Section: Methodsmentioning
confidence: 99%
“…RDW is a hematologic parameter that indicates the divergence of red blood cell volume. Increases in RDW have been found in different physiological and pathological conditions such as pregnancy, vitamin B12 and folate de ciency, malignancy, idiopathic pulmonary brosis and coronary artery disease (7)(8)(9)(10)(11)(12). Although RDW was created for the diagnosis of different types of anemia, recent research has revealed its predictive role in cerebrovascular diseases (13).…”
Section: Introductionmentioning
confidence: 99%
“…RDW is a hematologic parameter that indicates the divergence of red blood cell volume. Increases in RDW have been found in different physiological and pathological conditions such as pregnancy, vitamin B12 and folate deficiency, malignancy, idiopathic pulmonary fibrosis and coronary artery disease (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%